Anti-Inflammatory Activity of Oxyresveratrol Tetraacetate, an Ester Prodrug of Oxyresveratrol, on Lipopolysaccharide-Stimulated RAW264.7 Macrophage Cells - Wuttinont Thaweesest; Visarut Buranasudja; Rianthong Phumsuay; Chawanphat Muangnoi; Opa Vajragupta; Boonchoo Sritularak; Paitoon Rashatasakhon; Pornchai Rojsitthisak (Molecules, 2022)
Oxyresveratrol (OXY) has been reported for its anti-inflammatory activity; however, the pharmaceutical applications of this compound are limited by its physicochemical properties and poor pharmacokinetic profiles. The use of an ester prodrug is a promising strategy to overcome these obstacles. In previous researches, several carboxylate esters of OXY were synthesized and oxyresveratrol tetraacetate (OXY-TAc) was reported to possess anti-melanogenic and anti-skin-aging properties. In this study, in addition to OXY-TAc, two novel ester prodrugs of OXY, oxyresveratrol tetrapropionate (OXY-TPr), and oxyresveratrol tetrabutyrate (OXY-TBu), were synthesized. Results from the Caco-2-permeation assay suggested that synthesized ester prodrugs can improve the membrane-permeation ability of OXY. The OXY-TAc exhibited the most significant profile, then this prodrug was chosen to observe anti-inflammatory activities with lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. Our results showed that OXY-Tac significantly alleviated secretion of several pro-inflammatory mediators (nitric oxide (NO), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α)), mitigated expression of enzyme-regulated inflammation (inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2)), and suppressed the MAPK cascades. Interestingly, the observed anti-inflammatory activities of OXY-TAc were more remarkable than those of its parent compound OXY. Taken together, we demonstrated that OXY-TAc improved physicochemical and pharmacokinetic profiles and enhanced the pharmacological effects of OXY. Hence, the results in the present study would strongly support the clinical utilities of OXY-TAc for the treatment of inflammation-related disorders.